Legal Framework for Pontocaspian Biodiversity Conservation in the Danube Delta (Romania and Ukraine) - Gogaladze, Aleksandre; Biesmeijer, Jacobus C.; Son, Mikhail O.; Marushchak, Oleksii; Wesselingh, Frank P.; Lattuada, Matteo; Sandu, Cristina; Albrecht, Christian; Mihailescu, Simona; Raes, Niels (Frontiers in Conservation Science, 2022)
The declining biodiversity has upsetting consequences for social and economic development and represents a major concern for humanity. Legal and political framework plays an important role in biodiversity conservation planning, implementation and coordination of actions. Legal provisions are complex and operate on different levels of governance (from supranational to national), which means that the status of single species or populations may be governed by a set of interacting or even conflicting regulations, with increasing complexity for species that occur across national borders. Romania (EU member state) and Ukraine (non-EU member state) exemplify neighboring countries with different governance systems, which share the same endemic aquatic communities inhabiting the transitional zones between freshwater and marine ecosystems, known regionally as Pontocaspian (PC) biota. These communities include flagship species such as sturgeons and less-known crustaceans and mollusks and are severely threatened as a result of human activities. We assessed the legal basis for the protection of PC biota in the Danube Delta and the effectiveness of current conservation approaches based on a review of legal documents and literature, expert opinion and practitioner reflections regarding PC biodiversity conservation. We found that PC invertebrate species are not adequately addressed in the current legal documents and that the surrogate approach (where protection of umbrella species results in protection of background species) does not work as there is little overlap between the habitats of sturgeons and PC invertebrate communities. Furthermore, the habitat definitions currently used in legal documents lack the level of detail needed to protect PC habitats that are characterized by specific salinity (brackish) conditions. We finish by sketching out recommendations towards improved legal and political frameworks for effective and efficient conservation of PC invertebrate biota.